THE EFFECTIVENESS OF EXPAND GAMA TOWARD STUDENTS’ MOTIVATION IN LEARNING GRAMMAR - Lailatul Wardiah (Journal of Languages and Language Teaching, 2016)
This research was aimed to find out whether the use of expand game effective toward students’ motivation in learning grammar and to find out correlation between students’ motivation and grammar. The kind of this research was experimental research with pre test and post test design. The population of this research was the students at the second grade students of of MTs Al-Muslimun NW Tegal consist of 104 students. The sample of this research used two classes namely experimental group and control group where each group consisted of 26 students. The sample technique used in this research was cluster random sampling by using lottery. The experimental was taught by expand game and control group taught by puzzle game. The instruments that used were grammar test and questionnaire for the motivation. The data analyzed used t-test. The result of the analyzed showed that the value of to (t obtained) 3.50 was higher than tt (t table) 2.056, the significant level 0.05. Based on the result of the study, it could be concluded that the use of expand game effective in learning grammar at the Second Grade Students of MTs Al-Muslimun NW Tegal and the result correlation between students’ motivation and grammar showed r-test was higher than r-table (0.979 > 0.388). Based on the result of the study, it could be concluded that is correlation between students’ motivation and grammar is accepted. In other word, alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected.